2019
DOI: 10.1088/1402-4896/ab2d45
|View full text |Cite
|
Sign up to set email alerts
|

Quantum coherence recovery through Stern–Gerlach erasure

Abstract: Quantum erasure probes the dynamic nature of quantum coherence. It allows quantum systems to exhibit interference effects by recovering coherence that was previously lost through entanglement with another system. In this paper we examine the concept of a quantum eraser which creates and then erases path information through repeated use of the Stern–Gerlach effect. We explore the degree to which this eraser can recover quantum coherence. We find that the recovered coherence depends on the spin of the objects pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The quantum eraser has now been experimentally realized by various people using photons [14][15][16][17][18][19][20][21][22][23][24]. There have been some other proposals using neutral kaons [25], via a modified Stern-Gerlach setup [26,27], and also using atoms in an optical Stern-Gerlach model [28]. The idea of the quantum eraser has also been generalized to three-path interference [29].…”
Section: Introductionmentioning
confidence: 99%
“…The quantum eraser has now been experimentally realized by various people using photons [14][15][16][17][18][19][20][21][22][23][24]. There have been some other proposals using neutral kaons [25], via a modified Stern-Gerlach setup [26,27], and also using atoms in an optical Stern-Gerlach model [28]. The idea of the quantum eraser has also been generalized to three-path interference [29].…”
Section: Introductionmentioning
confidence: 99%
“…With the advances in experimental techniques the quantum eraser, with or without delayed-choice, was realized in various ways [15][16][17][18][19][20][21][22][23][24][25][26], and several other proposals were made [27][28][29][30]. It has also been demonstrated that the idea of quantum eraser should also work for three-path interference [31].…”
Section: Introductionmentioning
confidence: 99%